The effects of journal writing on efl learners' writing accuracy and fluency - Trần Thị Thanh Tuyền (Trường Đại học Trà Vinh, 2021)
The present study aims to investigate the effects of journal writing on EFL students’ writing accuracy. The present study aims to investigate the effects of journal writing on EFL students’ writing fluency. The present study aims to identify EFL students’ perspectives toward journal writing practice